(3LGeY GdebGUO aj TQM GdbhGYOs - (3GdcQcj, GdYGedj, CHh GdMSf, GdeMbb GdKGfj, Ydj Hf GdMSjf Hf YHO GdYGdj, J (B940(3g`s
(3ChdgG (B:s
(3caGQI GdbJd(B... (3aj QeVGf (B... (3hbO LYdg GdfHj ehLHG ddYJb ef GdfGQ abGd(B... (3hbhdg(B: (3hjJNU GdQb HCgd GdLRjQI Ohf GdjghO hGdfUGQi hGdeLhS hGdbGFejf HTQGFW GdPeI(B...s
(3BNQgG (B:s
(3bhdg(B: (3hgd jDNP ef Gdehdi eY hLhO GdYUHI GdCTHg fYe(B... (3jMed YUHI Ke eYJb GdeYJb (B... (3hgcPGs
(3JHUQI GdYfhGf (B:s
(3LGeY GdebGUOs
(3JHUQI GdeDda (B:s
(3GdeTghQ HGdeMbb GdKGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B430s
Keywords: (3abg GdePGgH GdCNQis